The Effectiveness of A Studdent Facilitator and Explaining Learning Model With A Roundhouse Diagram on Studdent Activity and Achievement in Virus Material - Wahyuningtyas, Arini Tri; Yuniastuti, Ari; Utami, Nur Rahayu (Journal of Biology Education, 2022)
Results of the observation shows that students are still passive during the learning process in which influence their learning achievement. A learning model of Student Facilitator and Explaining (SFaE) is effective to make the students explain the materials to their friends also to train students in expressing their ideas bravely. This study combines SFaE with Roundhouse diagram that makes students easier to understand and explain the materials of learning. The research was conducted for the tenth grade students of SMA N 1 Jekulo. A purposive sampling was used as the sampling technique, and two classes were used as the sample. The T-test shows that the t-value is more than t-table for 2.71 > 1.67 with which means H0 is rejected. This condition means that the average results of the experimental class is higher than the control class. The results of analysis on students’activity in the experimantal class is around 91.76% students are in the category of active until very active, and 8.33% are in the category of medium. In the control class, around 80.56% students are in the category of active until very active, and 19.44% are in the category of medium. In conclusion, the use of learning model Student Facilitator and Explaining (SFaE) with a Roundhouse diagram is effective to improve students’activity and achievement in the learning material of Virus.